Creative Accounting - Li, Lin (2006)
This dissertation studies the area of creative accounting. The investigation of the literature review initially concerns about the definition, motivations, existence and effect and the involved accounting standards of creative accounting Based upon that, the qualitative research is going to be carried through, with the Finance and Investment students of Nottingham University as participants, in order to capture information of views on creative accounting. Then the important part of the paper is the detailed discussion of the practical methods of creative accounting, following an overall analysis of the case of Enron's collapse. Finally, conclusions are being derived on the areas having been discussed and researched, the study's limitations and also some brief suggestions for future study.